Active versus restrictive ligation strategy for patent ductus arteriosus – A retrospective two-center study of extremely preterm infants born between 22 + 0 and 25 + 6 weeks of gestational age - Söderström, Fanny; Sindelar, Richard; Olsson, Karl Wilhelm; Yousef, Sawin; Todorova, Daniela; Pestalozzi, Joanna; Mellander, Mats; Raaijmakers, Renske (Early human development, 2024)
Patent ductus arteriosus (PDA) in premature infants is associated with adverse clinical outcomes. Mode and timing of treatment are still controversial. Data are limited in the most extremely premature infants <26 weeks of gestational age (GA), where clinical problems are most significant and patients are most vulnerable. To investigate whether different approaches to surgical closure of PDA in two large Swedish centers has an impact on clinical outcomes including mortality in extremely preterm infants born <26 weeks GA. Retrospective, two-center, cohort study. Infants born at 22+0–25+6 weeks GA between 2010 and 2016 at Uppsala University Children's Hospital (UUCH; n = 228) and Queen Silvia Children's Hospital Gothenburg (QSCHG; n = 220). Survival, bronchopulmonary dysplasia (BPD), and retinopathy of prematurity (ROP). Surgical closure of PDA was more common and performed earlier at QSCHG (50 % vs 16 %; median age 11 vs 44 days; p < 0.01). Survival was similar in both centres. There was a higher incidence of severe BPD and longer duration of mechanical ventilation at UUCH (p < 0.01). There was a higher incidence of ROP, IVH and sepsis at QSCH (p < 0.05, p < 0.01 and p < 0.01). A sub-group analysis matching all surgically treated infants at QSCHG with infants at UUCH with the same GA showed similar results as the total cohort. Earlier and higher rate of surgical PDA closure in this cohort of extremely preterms born <26 weeks GA did not impact mortality but was associated with lower rates of severe BPD and higher rates of severe ROP. •Lower gestatational age is the most important factor with regard to adverse outcomes of PDA•There is no consensus on optimal treatment and data in infants <26 weeks are scarce•This study compares different treatment strategies in this specific patient group•Earlier and higher rate of surgical PDA closure was associated with less severe BPD•Earlier and higher rate of surgical PDA closure was associated with more severe ROP